Romansko-germanska glagolska prepletanja v kraškem in istrskem narečnem prostoru - Cossutta, Rada (Annales. Series historia et sociologia, 2008)
The paper analyses Romance and Germanic verbal elements used in the Karstic and Istrian dialect areas from the points of view of morphology and lexicology. In the field of morphology, the paper sheds light on constant adaptation of Romance and Germanic borrowings to Slovene conjugation patterns, which is evident in particular from the following phenomena: 1) addition of Slovene verbal prefixes and suffixes to Romance-Germanic bases; 2)adoption of Slovene verbal endings or, more precisely, Slovene infinitive endings; 3) changes in aspectč 4) formation of the descriptive and passive participle ending in -n/-t from borrowed verbal bases. In the field of lexicology, the paper reveals the diverse lexical palette of Romance and Germanic borrowings and establishes their meaning and semantic changes. It places special emphasis on calques of Romance origin, which are mostly expressive formations and concrete proof of the interferencial richness of Karstic and Istrian dialect vocabulary
Keywords: dialect; Križ; narečja; Slovene; Slovenian Istria; Slovenska Istra; slovenščina